A phase I study of histone deacetylase inhibitor, pracinostat (SB939), in pediatric patients with refractory solid tumors: IND203 a trial of the NCIC IND program/C17 pediatric phase I consortium. Issue 11 (25th July 2013) - Zorzi, Alexandra P.; Bernstein, Mark; Samson, Yvan; Wall, Donna A.; Desai, Sunil; Nicksy, Darcy; Wainman, Nancy; Eisenhauer, Elizabeth; Baruchel, Sylvain
Abstract Background Pracinostat (SB939) is a potent oral inhibitor of class 1, 2, and 4 histone deacetylases (HDAC). The adult recommended phase II dose (RP2D) is 60 mg po three times per week (t.i.w.) for 3 weeks every 4 weeks. This study assessed the toxicities and pharmacokinetics of pracinostat and determined the RP2D in children with refractory solid tumors. Methods Pediatric patients with refractory solid tumors were treated with oral pracinostat t.i.w. for 3 consecutive weeks, followed by 1 week off dosing. Three dose levels—25, 35, and 45 mg/m2 were evaluated using a standard 3 + 3 cohort design. Pharmacokinetic (PK) studies were optional. Results Twelve patients were enrolled. The most common diagnosis was Ewing sarcoma. Most adverse events (AEs) were hematological with five (40%) patients experiencing grade 3 neutropenia. Non‐hematological AEs were generally grade 1. No dose limiting toxicities occurred. More hematological and non‐hematological AEs occurred at 45 mg/m2: Two of five patients experienced Grade 3 neutropenia and one each Grade 3 thrombocytopenia and leucopenia, Grade 1 fatigue and anorexia occurred in three. The RP2D was declared to be 45 mg/m2 (comparable to an adult dose of 80 mg). One patient had a best response of stable disease (duration of 2.9 months). Three patients on 25 mg/m2 and one each on 35 and 45 mg/m2 participated in the PK study. No dose related changes in Cmax or AUC occurred. Conclusions Pracinostat is reasonably well tolerated in children with refractory solid tumors. The RP2D is 45 mg/m2. Pediatr Blood Cancer 2013;60:1868–1874. © 2013 Wiley Periodicals, Inc.